2017
DOI: 10.1111/pere.12174
|View full text |Cite
|
Sign up to set email alerts
|

Relational mobility and close relationships: A socioecological approach to explain cross‐cultural differences

Abstract: This article reviews how behaviors and psychological tendencies in close relationships differ between cultures, and proposes a socioecological framework to understand those differences. Our review of the literature finds that paradoxically, people in individualistic cultures are more actively engaged in close relationships (e.g., higher levels of social support, self-disclosure, intimacy, and love) than those in collectivistic cultures. From an adaptationist perspective, we argue that one reason for these diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 72 publications
0
58
0
1
Order By: Relevance
“…Based on previous dual-country studies, we tested a number of confirmatory hypotheses about the psychological and behavioral outcomes of relational mobility in the 39-society dataset. We theorize that generalized trust ( 10 , 24 ) and self-esteem ( 25 ) should be higher in relationally mobile societies, because they give people confidence to approach new desirable people in an open and competitive interpersonal marketplace ( 3 , 7 , 8 ). Hence, trust and self-esteem help people achieve the task of acquiring desirable relationships ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous dual-country studies, we tested a number of confirmatory hypotheses about the psychological and behavioral outcomes of relational mobility in the 39-society dataset. We theorize that generalized trust ( 10 , 24 ) and self-esteem ( 25 ) should be higher in relationally mobile societies, because they give people confidence to approach new desirable people in an open and competitive interpersonal marketplace ( 3 , 7 , 8 ). Hence, trust and self-esteem help people achieve the task of acquiring desirable relationships ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, studies have found that differences in relational mobility can explain societal differences, such as generalized trust, self-enhancement, self-disclosure, intimacy, and need for uniqueness ( 7 ). In this way, previous studies have shown that relational mobility drives differences between societies in how people act, think, and feel ( 8 , 16 ).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Given the high relational mobility, active relationship maintenance is required in this cultural context, and sharing memory is considered an effective means to achieve the purpose (Chen, 1995;Kito, 2005;Wang, 2013). In comparison, in many Asian cultures, relationships are largely defined by geographical vicinity or circumstances of birth, and therefore tend to be more stable and require less maintenance through means such as memory sharing (Brint, 2001;Kito, Yuki & Thomson, 2017). Indeed, European American individuals report sharing memoriesparticularly specific autobiographical memories -more frequently than do Asians for social bonding purposes (Kulkofsky, Wang, & Hou, 2010;Kulkofsky, Wang, & Koh, 2009;Schug, Yuki, & Maddux, 2010).…”
Section: Culture Memory Sharing and Relationship Closenessmentioning
confidence: 99%
“…Germany represents a rather individualistic country (score 67), whereas Japan characterizes a mid-range collectivistic country (score 46). Although Japan does not represent an extreme collectivistic country based on this dimension (and becomes more individualistic, Ogihara, 2017), there is a wide range of research showing the persistence of collectivism in Japan, especially the importance of collectivistic living (increased importance in social obligation, social harmony, and social contribution and decreased importance in individual rights; e.g., Hamamura, 2012;Kito, Yuki, & Thomson, 2017;Ogihara, 2017), and low levels of relational mobility (e.g., Thomson et al, 2018).…”
Section: The Present Researchmentioning
confidence: 99%